A Protective Role of FAM13A in Human Airway Epithelial Cells Upon Exposure to Cigarette Smoke Extract - Chen, Qing; de Vries, Maaike; Nwozor, Kingsley Okechukwu; Noordhoek, Jacobien A.; Brandsma, Corry-Anke; Boezen, H. Marike; Heijink, Irene H. (Frontiers in Physiology, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by chronic inflammation upon inhalation of noxious particles, e.g. cigarette smoke. FAM13A is one of the genes often found to be associated with COPD, however its function in the pathophysiology of COPD is incompletely understood. We studied its role in airway epithelial barrier integrity and cigarette smoke-induced epithelial responses. Methods: Protein level and localization of FAM13A was assessed with immunohistochemistry in lung tissue from COPD patients and non-COPD controls. In vitro, FAM13A expression was determined in the absence or presence of cigarette smoke extract (CSE) in primary airway epithelial cells (AECs) from COPD patients and controls by western blotting. FAM13A was overexpressed in cell line 16HBE14o- and its effect on barrier function was monitored real-time by electrical resistance. Expression of junctional protein E-cadherin and β-catenin was assessed by western blotting. The secretion of neutrophil attractant CXCL8 upon CSE exposure was measured by ELISA. Results: FAM13A was strongly expressed in airway epithelium, but significantly weaker in airways of COPD patients compared to non-COPD controls. In COPD-derived AECs, but not those of controls, FAM13A was significantly downregulated by CSE. 16HBE14o- cells overexpressing FAM13A built up epithelial resistance significantly more rapidly, which was accompanied by higher E-cadherin expression and reduced CSE-induced CXCL8 levels. Conclusion: Our data indicate that the expression of FAM13A is lower in airway epithelium of COPD patients compared to non-COPD controls. In addition, cigarette smoking selectively downregulates airway epithelial expression of FAM13A in COPD patients. This may have important consequences for the pathophysiology of COPD, as the more rapid build-up of epithelial resistance upon FAM13A overexpression suggests improved (re)constitution of barrier function. The reduced epithelial secretion of CXCL8 upon CSE-induced damage suggests that lower FAM13A expression upon cigarette smoking may facilitate epithelial-driven neutrophilia.